The Meaning of Life and Religious Coping in the Fight Against Cancer: A Study with Oncology Patients in Brazil in Light of Viktor Frankl's Theory - Bueno Bejarano Vale de Medeiros, Angelica Yolanda (Journal of religion and health, 2024)
This study aimed to describe the perception of the meaning of life and coping strategies of 19 patients with cancer at a public hospital in Brazil. This is descriptive and qualitative research that used Amedeo Giorgi's phenomenological model, and the interpretation was performed in light of Viktor Frankl's theory. Two themes have emerged: (1) the perception of the meaning of life in the experience with cancer and (2) religious coping to fight the disease. This study showed that revealing the meaning of life in the cancer experience contributes to better treatment compliance, a more favorable view of the future and better quality of life. On the other hand, religious coping is the strategy most used by patients who believe in God, showing a greater state of psychological and spiritual well-being.